Analisis Pengaruh Stres Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Bagian Biro Sumber Daya Manusia Aparatur Dan Organisasi Badan Narkotika Nasional Republik Indonesia Di Jakarta - Indah Putri Amelia; Lukman Hakim; Iwan Supriyanto (PT. Karya Inovatif Nusantara, 2025)
This study aims to analyze the influence of work stress and work discipline on employee performance in the Bureau of Human Resources for Apparatus and Organization of the National Narcotics Agency of the Republic of Indonesia in Jakarta. This study uses a quantitative approach, with all employees of the Bureau of Human Resources for Apparatus and Organization as many as 65 people as respondents. Data were collected through questionnaires and analyzed using multiple linear regression test methods with the help of SPSS. The results obtained indicate that work stress partially does not have a significant effect on employee performance, with a t-value of 0.857 and a significance of 0.395. This means that the level of stress felt by employees does not directly reduce or increase their performance. Meanwhile, work discipline has proven to have a significant effect, indicated by a t-value of 3.850 and a significance value of 0.001. When tested together, work stress and work discipline have a significant effect on performance, with F count of 9.359 and significance of 0.001. The contribution of both variabels to employee performance is 23.2%.